Fruit quality of 'Stanley' plums based on soil composition across diverse agro-ecological zones of Morocco - Mrabet , Oumaima; Asbai, Zakaria; Hadidi, Meryem; Bahlaouan , Bouchaib; Tesse , Rajaa; ElAntri, Said; Boutaleb, Nadia (Comunicata Scientiae, 2024)
The national production of plums, especially prunes, is strongly increasing, attracting attention in the local market. This study aims to assess the impact of soil chemical composition on the nutritional and physicochemical quality of plums of the variety ''STANLEY'' (Prunus Domestica L.) across diverse agro-ecological zones of Morocco. Through a preliminary survey of 21 growers in three distinct regions: Sais, Atlas and Oriental. Supplemented by sampling at eight locations in eastern and western Morocco, three categories of parameters were considered in this study: (1) parameters related to cultivation conditions, including climate, geographical structuring, plot size and planting age; (2) those providing information on physico-chemical properties, nutritional value and sugar content; (3) parameters related to soil quality. The surveyed farmers are proprietors of cultivated plots ranging from 6 to 70 hectares, with an average yield of 12T/ h. Notably, 28% of producers with recently established plantations (less than 10 years) have achieved yields exceeding 15T/h, indicating the fertility of trees at this stage of maturity. The findings affirm that soil fertility and soil amendment are the major factors contributing to high-quality fruit (large caliber, high Brix rate, intact product…). Additionally, this study highlights the significance of climate and irrigation in achieving the desired quality of plums.